NURF301 contributes to gypsy chromatin insulator-mediated nuclear organization. Issue 14 (12th July 2022) - Chen, Shue; Rosin, Leah F; Pegoraro, Gianluca; Moshkovich, Nellie; Murphy, Patrick J; Yu, Guoyun; Lei, Elissa P
Abstract: Chromatin insulators are DNA-protein complexes that can prevent the spread of repressive chromatin and block communication between enhancers and promoters to regulate gene expression. In Drosophila, the gypsy chromatin insulator complex consists of three core proteins: CP190, Su(Hw), and Mod(mdg4)67.2. These factors concentrate at nuclear foci termed insulator bodies, and changes in insulator body localization have been observed in mutants defective for insulator function. Here, we identified NURF301/E(bx), a nucleosome remodeling factor, as a novel regulator of gypsy insulator body localization through a high-throughput RNAi imaging screen. NURF301 promotes gypsy -dependent insulator barrier activity and physically interacts with gypsy insulator proteins. Using ChIP-seq, we found that NURF301 co-localizes with insulator proteins genome-wide, and NURF301 promotes chromatin association of Su(Hw) and CP190 at gypsy insulator binding sites. These effects correlate with NURF301-dependent nucleosome repositioning. At the same time, CP190 and Su(Hw) both facilitate recruitment of NURF301 to chromatin. Finally, Oligopaint FISH combined with immunofluorescence revealed that NURF301 promotes 3D contact between insulator bodies and gypsy insulator DNA binding sites, and NURF301 is required for proper nuclear positioning of gypsy binding sites. Our data provide new insights into how a nucleosome remodeling factor and insulator proteins cooperatively contribute to nuclear organization.